2015
DOI: 10.11138/ccmbm/2015.12.3s.054
|View full text |Cite
|
Sign up to set email alerts
|

Locking plate fixation of distal femoral fractures is a challenging technique: a retrospective review

Abstract: Distal femoral fractures have typically a bimodal occurrence: in young people due to a high-energy trauma and in older people related to a low-energy trauma. These fractures are associated to a very high morbidity and mortality in elderly. Distal femoral fractures might be treated with plates, intramedullary nails, external fixations, and prosthesis. However, difficulties in fracture healing and the rate of complications are important clinical issues. The purpose of this retrospective review was to present our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The advent of locking plates (LP) represented a relevant evolution in the treatment of osteoporotic fractures. 29 Their use in PHF is potentially indicated for all reconstructable fractures, except in cases with significant comminution, head split or impaction that did do not allow a stable synthesis. It has been observed that patients with valgus impaction have better outcomes than those with varus impaction fractures.…”
Section: What Kind Of Fixation Should Be Used?mentioning
confidence: 99%
“…The advent of locking plates (LP) represented a relevant evolution in the treatment of osteoporotic fractures. 29 Their use in PHF is potentially indicated for all reconstructable fractures, except in cases with significant comminution, head split or impaction that did do not allow a stable synthesis. It has been observed that patients with valgus impaction have better outcomes than those with varus impaction fractures.…”
Section: What Kind Of Fixation Should Be Used?mentioning
confidence: 99%
“…With increased callus formation, the bone will transmit an increasing proportion of the load [56]. If fracture healing does not occur or is delayed, then the plate must support all applied loading and plate breakage will eventually occur [22]. Previous experimental studies that have considered load-bearing scenarios have found that more rigid constructs perform better under cyclic loading [41,51,54,59].…”
Section: Effects Of Fracture Healingmentioning
confidence: 99%
“…It is well accepted that the majority of locked plating failures are due to inappropriate device configuration for the fracture pattern [21][22][23][24][25]. Several studies cite screw positioning variables such as the number and spacing of screws as responsible for cases of locking plate breakage, screw loosening, and periprosthetic re-fracture [3,8,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…He should know the fracture segments of condyles and any comminution in articular surface or metaphyseal segment. Sometimes it is better to bypass comminution with bridging technique (14). If you miss this comminution and open it, risk of nonunion will highly increase.…”
Section: Pitfalls In Operationmentioning
confidence: 99%